1991
DOI: 10.1111/j.1151-2916.1991.tb04081.x
|View full text |Cite
|
Sign up to set email alerts
|

Boron Carbide Reinforced Alumina Composites

Abstract: The mechanical properties of alumina have been successfully improved by adding isolated boron carbide particles of two different shapes. A K I , of 7.26 2 0.20 MPa-m"' for alumina-boron carbide whiskerlike composites and of 5.27 2 0.12 MPa. m"' alumina-boron carbide shardlike particle composites has been achieved. The fracture toughness of these composites is dependent on the volume fraction of the boron carbide particles as well as their size and shape. The flexural strength is also appreciably enhanced to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…Reinforcement with hard second‐phase particles is also known to produce an improvement in the fracture toughness through a variety of mechanisms such as grain bridging, phase transformations, etc. Thus, 5–20 vol% of TiC, B 4 C, or TiB 2 particles in hot‐pressed Al 2 O 3 ‐based composites resulted in the increase of fracture toughness from 4.0 to 4.5–6.5 MPa·m 0.5 31,32 . In the present study, a similar increase in fracture toughness is observed for STC‐1‐2 (SiC+TiC, K I c =5.6 MPa·m 0.5 ) compared with SC‐1 (SiC, K I c =4.4 MPa·m 0.5 ).…”
Section: Resultssupporting
confidence: 82%
“…Reinforcement with hard second‐phase particles is also known to produce an improvement in the fracture toughness through a variety of mechanisms such as grain bridging, phase transformations, etc. Thus, 5–20 vol% of TiC, B 4 C, or TiB 2 particles in hot‐pressed Al 2 O 3 ‐based composites resulted in the increase of fracture toughness from 4.0 to 4.5–6.5 MPa·m 0.5 31,32 . In the present study, a similar increase in fracture toughness is observed for STC‐1‐2 (SiC+TiC, K I c =5.6 MPa·m 0.5 ) compared with SC‐1 (SiC, K I c =4.4 MPa·m 0.5 ).…”
Section: Resultssupporting
confidence: 82%
“…The addition of TiC, TiB 2 , WC or SiC particles in an Al 2 O 3 matrix improve the fracture toughness, hardness, and strength for cutting tool applications [8][9][10][11][12]. The mechanical properties of Al 2 O 3 were successfully improved with addition of 5-20 vol.% of whisker like and shardlike shaped B 4 C particles [13]. Moreover, small amounts of SiC were found to significantly improve the strength of Al 2 O 3 -based ceramics [11,12,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Free carbon and oxygen participate in the formation of this phase, and carbon suboxide releases. According to [3,17], the following ternary phases are revealed in the (B 4 C + Al) composites: Al 4 BC, AlB 12 C 2 , and AlB 24 C 4 . As the thermodynamic calculations in [18] demonstrate, the formation of ternary compounds with a high boron content in the Al-B-C system at temperatures above 1300°C becomes more efficient than of binary aluminum carbides and borides.…”
mentioning
confidence: 99%